Phytochemical Characterization of White Turmeric (Curcuma mangga Val.) Extract as a Candidate Natural Immunostimulant for Aquatic Organisms - Ulaan, Magdalin; Mose, Numisye I.; Indriani, Yeni; Saselah, Jetti T.; Manganang, Yessi A. P (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
The increasing intensity of aquaculture practices has elevated the risk of disease outbreaks, which may negatively affect aquaculture productivity. The use of natural products containing bioactive compounds represents a promising strategy for improving the health status of aquatic organisms. This study aimed to characterize the phytochemical constituents of white turmeric (Curcuma mangga Val.) extract to identify bioactive compounds with potential applications as natural immunostimulants in fish feed. The extraction process was carried out using 250 g of white turmeric powder by the maceration method. The resulting extract was subsequently filtered, concentrated using a rotary evaporator, and subjected to phytochemical screening based on colorimetric assays. Phytochemical analysis revealed that white turmeric tested positive for the presence of flavonoids, alkaloids, saponins, and tannins. The findings indicate that white turmeric extract has considerable potential as a natural source of bioactive compounds for incorporation into fish feed formulations. Nevertheless, further studies are required to evaluate its effects on immune responses, growth performance, and disease resistance in aquatic organisms.